Two new species of Amblypsilopus Bigot with a key to species from Vietnam (Diptera: Dolichopodidae) - Li, Xuankun; Li, Zhu; Yang, Ding (Zootaxa, 2013)
Eight species of the genus Amblypsilopus Bigot are now recorded from Vietnam. The following two new species are described: Amblypsilopus lacduonganus sp. nov. and A. longus sp. nov. Two species, A. basalis Yang and A. capitatus Yang, are newly reported fromVietnam. A key to the species of the genus fromVietnam is provided.